Intermediation frictions in debt relief: Evidence from CARES Act forbearance - You Suk Kim; Donghoon Lee; Tess Scharlemann; James Vickery (Federal Reserve Bank of New York, 2022)
We study how intermediaries-mortgage servicers-shaped the implementation of mortgage forbearance during the COVID-19 pandemic and use servicer-level variation to trace out the causal effect of forbearance on borrowers. Forbearance provision varied widely across servicers. Small servicers and nonbanks, especially nonbanks with small liquidity buffers, facilitated fewer forbearances and saw a higher incidence of forbearance-related complaints. Easier access to forbearance substantially increased mortgage nonpayment but also reduced delinquencies outside of forbearance. Part of the liquidity from forbearance was used to reduce credit card debt, but most was saved or used for nondurable consumption.
Keywords: G21; G23; G28; 330; mortgage; forbearance; liquidity; nonbank; CARES Act; COVID-19